Hospitable Education—Interreligious Education Revisited - Ina ter Avest (Religions)
In the past, the Netherlands took on the form of a pillarized society, with three ‘pillars’ (Catholic, Protestant and liberal) ‘living apart together’. Each pillar came with its own education system, health care, and newspapers. In the 1980s, a fourth ‘pillar’ was added: the Islamic pillar. During the same period at the end of the 20th century, a model was developed at one of the country’s primary schools—the Juliana van Stolberg school—for the inclusive interreligious education of all pupils, irrespective of the (religious or secular) life orientation of their parents. This innovative educational process became the object of research. Literature reviews on (inter)religious education were complemented by qualitative interviews with the school’s principal and supplemented with historical research of the school’s filing cabinet kept in the city archives. I conclude that by revisiting the process and the developed model of inclusive interreligious education, its implementation in all schools is possible, provided that the latest insights are taken into account about leadership, biblical and qur’anic hermeneutics and the position of parents in the pedagogic civil society. For such an adapted model, I introduce the concept of hospitable education—hospitality as a competence, which connects knowledge, affective attitudes and skills.